Surface integrity study of shot peened IN718 - Nur Harith Bin Sazeli (Nanyang Technological University, 2024)
With a nickel-chrome base, Inconel 718 (IN718) is a unique kind of high-strength superalloy that is resistant to corrosion, high pressure, and extreme temperatures. A wide number of industries, including manufacturing, aerospace, and military equipment, have found use for IN718 due to its special qualities. IN718 is a common component for turbojet engine parts such as compressor casings, discs, and fan blades because of its strength and resistance. Because of the superalloy's great heat resistance, it is also used in the manufacture of rocket engines. This is the main explanation for why roughly half of the parts in typical aircraft engine parts are made of Inconel 718. Additive manufacturing (AM) of IN718 has emerged as a transformative technology offering unique advantages to produce complex components in aerospace, automotive, and other high-performance applications. This study explores the characteristics and implications of AM in the fabrication of IN718 components, focusing on its microstructural evolution, mechanical properties, and impact on performance. Through selective laser melting (SLM), intricate IN718 geometries are produced layer by layer, enabling design freedom and reducing material waste. The resulting microstructure is scrutinised using advanced techniques such as scanning electron microscopy (SEM). The microstructural features, including the presence of grain boundaries and precipitates, are analysed in relation to the processing parameters. The study also investigates the impact of surface integrity variation on IN718 after shot peening, and the correlation of the process parameters with surface integrity through various material and mechanical characterization techniques. Additionally, the research explores the challenges associated with AM of IN718, including build orientation effects, microstructural anisotropy, and the potential for defects such as porosity and lack of fusion. Strategies to mitigate these challenges and optimize the AM process for IN718 are discussed.